Neutrophil to lymphocyte ratio (NTLR) predicts local control and overall survival after stereotactic body radiotherapy (SBRT) in metastatic sarcoma - Eashwar Somasundaram; Peter M. Anderson; Timothy D. Smile; Ahmed Halima; James B. Broughman; Chandana A. Reddy; Shireen Parsai; Jacob G. Scott; Timothy Chan; Shauna Campbell; Lilyana Angelov; Stacey Zahler; et al. (Scientific Reports, 2023)
Abstract The neutrophil to lymphocyte ratio (NTLR) and absolute lymphocyte count (ALC) recovery are prognostic across many cancers. We investigated whether NLTR predicts SBRT success or survival in a metastatic sarcoma cohort treated with SBRT from 2014 and 2020 (N = 42). Wilcox Signed Rank Test and Friedman Test compare NTLR changes with local failure vs. local control (N = 138 lesions). Cox analyses identified factors associated with overall survival. If local control was successful, NLTR change was not significant (p = 0.30). However, NLTR significantly changed in patients with local failure (p = 0.027). The multivariable Cox model demonstrated higher NLTR before SBRT was associated with worse overall survival (p = 0.002). The optimal NTLR cut point was 5 (Youden index: 0.418). One-year overall survival in SBRT metastatic sarcoma cohort was 47.6% (CI 34.3%–66.1%). Patients with an NTLR above 5 had a one-year overall survival of 37.7% (21.4%–66.3%); patients with an NTLR below 5 had a significantly improved overall survival of 63% (43.3%–91.6%, p = 0.014). Since NTLR at the time of SBRT was significantly associated with local control success and overall survival in metastatic sarcoma treated with SBRT, future efforts to reduce tumor inhibitory microenvironment factors and improve lymphocyte recovery should be investigated.